Time to reconsider the role of ribavirin in Lassa fever. - Alex Paddy Salam; Vincent Cheng; Tansy Edwards; Piero Olliaro; Jonathan Sterne; Peter Horby (PLoS Neglected Tropical Diseases)
Ribavirin is the only available Lassa fever treatment. The rationale for using ribavirin is based on one clinical study conducted in the early 1980s. However, reanalysis of previous unpublished data reveals that ribavirin may actually be harmful in some Lassa fever patients. An urgent reevaluation of ribavirin is therefore needed.